Raman in situ characterization of the species present in Co/CeO2 and Co/ZrO2 catalysts during the COPrOx reaction - Gómez, Leticia Ester (2016)
The in situ Raman spectroscopy constitutes a powerful procedure to characterize catalytic surfaces under reaction conditions. In this work, we studied the species present in Co/CeO2 and Co/ZrO2 catalysts during the COPrOx reaction carried out between room temperature and 500 °C. For both catalysts, TPR and Raman results suggest that a redox mechanism proceeds in which the reduction step with either hydrogen or CO is the rate-limiting step. The CeO2 support is better than the ZrO2 one because the former accelerates the surface exchange between reduced and oxidized species due to the high mobility of surface lattice oxygen and the presence of oxygen vacancies. The Ce4+ + Co2+ ↔ Ce3+ + Co3+ process acts as a buffer effect by which Co3+, which is the active species in this reaction, is always present even in a reducing atmosphere, as shown by in situ Raman characterization.